Maritime Autonomous Vessels (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is a printed edition of the Special Issue on Maritime Autonomous Vessels that was published in the Journal of Marine Science and Engineering. It contains an editorial and 17 peer-reviewed research studies in the field of Maritime Autonomous Surface Ships (MASS), Unmanned Surface Vessels (USVs), Autonomous Underwater Vehicles (AUVs), and underwater gliders, to name a few. The main goal of this reprint is to address key challenges, thereby promoting research on marine autonomous ships. There are many topics on autonomous vessels involved in this reprint, for instance, automatic control, manoeuvrability, collision avoidance, ship target identification, motion planning, and buckling analysis.